2021
DOI: 10.3389/fgene.2021.617505
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Microbiome Co-expression Networks in Colon Cancer

Abstract: It is known that cancer onset and development arise from complex, multi-factorial phenomena spanning from the molecular, functional, micro-environmental, and cellular up to the tissular and organismal levels. Important advances have been made in the systematic analysis of the molecular (mostly genomic and transcriptomic) within large studies of high throughput data such as The Cancer Genome Atlas collaboration. However, the role of the microbiome in the induction of biological changes needed to reach these pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Studies on the bacterial or viral composition of human tumors using sequencing data from databases such as the TCGA have recently emerged ( 14 , 20 ). Investigation of the intratumor microbiota will provide valuable information for better understanding the occurrence and progression of tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the bacterial or viral composition of human tumors using sequencing data from databases such as the TCGA have recently emerged ( 14 , 20 ). Investigation of the intratumor microbiota will provide valuable information for better understanding the occurrence and progression of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we explored the microbiota signature in four major types of gastrointestinal cancer, and the results demonstrated that the microbial profile is highly site-specific and notably differed between upper and lower gastrointestinal tumors ( 12 ). Several other studies have also investigated the intratumor microbiota derived from TCGA sequences of different cancer types ( 13 , 14 ). In the study of a TCGA breast cancer cohort, the results indicated an increased Proteobacteria presence in tumor tissues, while the composition of Actinobacteria was elevated in the adjacent normal tissues ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a study analyzed publicly available data to determine if the composition of microbiota affected host gene expression in early-stage CRC and advanced-stage CRC [59]. The bacterial taxa with more connections with the expression of host genes in early-stage CRC were Ilumatobacter, Rhodospirillum, and Nitrosospira, while in advanced-stage CRC they were Desulfurella, Nitriliruptor, and Jeotgalicoccus [59]. Indeed, these taxa are not the usual taxa associated with CRC.…”
Section: Transcriptionmentioning
confidence: 99%
“…Thus, this kind of novel approach is useful to unveil hidden biological mechanisms. In addition, the connected genes with these bacteria belonged to biological functions related to proliferation, biogenesis, and cell cycles in early-stage CRC, and related to migration and angiogenesis in advanced-stage CRC [59].…”
Section: Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation